Exposure to Ideas, Evaluation Apprehension, and Incubation Intervals in Collaborative Idea Generation - Zhou, Xiang; Zhai, Hong-Kun; Delidabieke, Bibi; Zeng, Hui; Cui, Yu-Xin; Cao, Xue (Frontiers in Psychology, 2019)
This study focused on the social factors and cognitive processes that influence collaborative idea generation, using the research paradigm of group idea generation, evaluation apprehension, and incubation. Specifically, it aimed to explore the impact of exposure to others' ideas, evaluation apprehension, and incubation intervals on collaborative idea generation through three experiments. The results showed that in the process of generating ideas in a group, exposure to others' ideas, and evaluation apprehension can lead to productivity deficits in the number and categories of ideas, without affecting the novelty of ideas. Further, exposure to others' ideas and evaluation apprehension had an interaction effect on the number of ideas. As compared with the situation without exposure to others' idea, in that with exposure to others' idea, evaluation apprehension had a weaker impact on the productivity of the number of ideas. Furthermore, incubation intervals were beneficial in reducing the negative effect of exposure to others' ideas and in improving collaborative idea generation productivity.